2008
DOI: 10.4049/jimmunol.181.5.3698
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Staphylococcus aureus Enterotoxin A Induces IFN-γ and CD8 T Cell-Dependent Airway and Interstitial Lung Pathology in Mice

Abstract: Staphylococcus aureus, a primary source of bacterial superantigen (SAg), is known to colonize the human respiratory tract and has been implicated in airway inflammation. Studies have documented a role for SAgs in respiratory disorders, such as nasal polyps, chronic obstructive pulmonary disease, chronic rhinosinusitis, and asthma. However, cellular and molecular mediators involved in SAg-mediated pulmonary disease have not been clearly identified. In this study, we investigated the effect of intranasal staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 33 publications
4
50
1
Order By: Relevance
“…Interestingly, SEA alone (with no OVA challenge) significantly increased the eosinophil influx into the lung section, as observed at 4 to 48 h preexposure. This is consistent with previous studies showing the presence of pulmonary inflammatory infiltrates in animals exposed to SEA alone (17,29,30). It is intriguing, however, that SEA exposure alone promotes eosinophil infiltration into the lung with no accompanying changes in BM and circulating blood.…”
Section: Vla4supporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, SEA alone (with no OVA challenge) significantly increased the eosinophil influx into the lung section, as observed at 4 to 48 h preexposure. This is consistent with previous studies showing the presence of pulmonary inflammatory infiltrates in animals exposed to SEA alone (17,29,30). It is intriguing, however, that SEA exposure alone promotes eosinophil infiltration into the lung with no accompanying changes in BM and circulating blood.…”
Section: Vla4supporting
confidence: 82%
“…The eosinophil progenitors are currently defined as CD34 ϩ cells that coexpress IL-5 receptor alpha (IL-5R␣) on their surface (5,19,35,40). IL-5 itself upregulates its receptor (IL-5R␣) on CD34 ϩ progenitor cells acting in an autocrine manner (13,21,30). Allergic stimulation elevates the serum levels of IL-5 that further enhances the expression of IL-5 receptor (IL-5R1), expanding to 10-to 20-fold (or even greater) the BM eosinophil progenitor, thus promoting their differentiation into mature cells for release into the peripheral blood (41).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory showed that intranasal (i.n.) SEA results in acute lung injury that depends on the activation of CD8 T cells and IFNγ, and importantly, this lung injury model also presents systemic effects (28). We tested if systemic pretreatment with poly(I:C) could mitigate the local and systemic responses to i.n.…”
Section: Poly(i:c) Pretreatment and Blocking The St2 Pathway Reduces mentioning
confidence: 99%
“…An alternative model proposed in this study is intranasal inhalation of the organic dust. Intranasal administration of other agents, including, but not limited to, ultrafine particles, biomass particles, bacterial components, microbial superantigens, and allergens, are becoming increasingly utilized to investigate mechanisms of exaggerated airway inflammation in vivo (10,15,22,24,26).…”
mentioning
confidence: 99%